Contemporary debates in applied ethics - Cohen, Andrew I.; Wellman, Christopher Heath (Malden, MA : Blackwell Pub., 2005)
"Contemporary Debates in Applied Ethics features original essays an some of the most hotly debated issues in the field. Is abortion morally permissible? Should we be allowed to clone human beings? Should immigration be limited, or left open?" "Showcasing original arguments for well-defined positions, as well as clear and concise statements of sophisticated philosophical views, this volume is an excellent resource for professional philosophers and students alike."--BOOK JACKET.
1. The wrong of abortion / Patrick Lee and Robert P. George -- 2. The moral permissibility of abortion / Margaret Olivia Little -- 3. A defense of affirmative action / Albert Mosley -- 4. Preferential policies have become toxic / Celia Wolf-Devine -- 5. Empty cages : animals rights and vivisection / Tom Regan -- 6. Animals and their medical use / R. G. Frey -- 7. A defense of the death penalty / Louis P. Pojman -- 8. Why we should put the death penalty to rest / Stephen Nathanson -- 9. Why I oppose human cloning / Jeremy Rifkin -- 10. The poverty of objections to human reproductive cloning / John Harris -- 11. In defense of voluntary active euthanasia and assisted suicide / Michael Tooley -- 12. A case against euthanasia / Daniel Callahan -- 13. Immigration : the case for limits / David Miller -- 14. The case for open immigration / Chandran Kukathas -- 15. The right to get turned on : pornography, autonomy, equality / Andrew Altman -- 16. "The price we pay"? : pornography and harm / Susan J. Brison -- 17. The limits of privacy / Amitai Etzioni -- 18. The case for privacy / David D. Friedman -- 19. The intrinsic value of nature in public policy : the case of the Endangered Species Act / J. Baird Callicott -- 20. Values in nature : a pluralistic approach / Bryan G. Norton -- 21. Famine relief : the duties we have to others / Christopher Heath Wellman -- 22. Famine relief and human virtue / Andrew I. Cohen.
Includes bibliographical references and index.
Keywords: Applied ethics